Uma Análise Semiótica da Evolução do Software - Bossolani, Carlos Augusto (2007)
The main motivation of this work was the growing popularization, among scientists, of a theory which asserts that the biological evolution may be guided by the cultural evolution. Known as the Baldwin Effect, it asserts that when things to be learned become relatively fixed, this creates an evolutionary pressure for those things to be incorporated genetically, by natural selection. The work started with the verification that there are several occurrences of an effect similar to the Baldwin Effect, where one, more flexible, evolutionary level guides the evolution of another level, less flexible. The problem approached by the research was the inexistence of a single explanation for these several occurrences. Of theses occurrences, the evolution of software was taken as the work s object of studies. Its teleological aspect can be more clearly appreciated by observing that the evolution of the programming languages is guided by the evolution of the programs, and that every program is written using a programming language. Since programs change more quickly as the languages, those more successful tend to be incorporated or to determine which characteristics should be present in the next generation of languages, guiding, in this manner, their evolution. Given the relationship between software and language, the main objective of the work is to demonstrate that the teleological aspect of the software evolution originate, mainly, from the role played by semiosis in it. Bibliographical research is used as the methodology of work, and the theoretical background used is Semiotics and other elements of Peirce s evolutionary philosophy. The work presents, at first, the theoretical foundations, explaining how evolution corresponds to the action of sign and why this process is teleological. Next, it approaches the software evolution presenting situations where this can be observed. By pointing a concrete situation where evolution is guided, and by demonstrating what this is caused by the action of sign, the work has contributed to the area of communication and semiotics in two manners: it makes evident the relationship between computation and semiosis and argues in favor of the importance of the sign action in evolution, calling attention to its teleological aspect